Revisiting The Strategy of Bata - Sari Wahyuni; Monica Devina; Annisa Anjani; Harrtyan Muhammad; Mohd Rifdi Safwan; Yohannes Ekaputra (Journal of International Conference Proceedings (JICP), 2018)
Indonesia is a very promising market for every consumer goods products. Bata, which has already gripped enormous market share in ASEAN countries, seems to be still wondering on how to conquer Indonesian market. The aim of this paper is to elaborate the strategy of Bata to attract potential customers and adapt with the tight competition in the retail industry. The methodology used for this paper is desk research or secondary research, such as annual report, websites, and e-books. The results revealed that the strategies should be taken through improving media channels, quality of products, and company’s image. Since Bata is in the maturity stage on the business life cycle, the key strategy to compete in the market is cost leadership. Keywords: business competition,consumer product, cost leadership strategy, maturity stage, retail industry